The equilibrium moisture of building enclosures as function of calculated climatic parameters/Pastatų atitvarinių konstrukcijų nuostoviojo drėgnio priklausomybė nuo skaičiuojamųjų klimato parametrų - Gnip, Ivan; Keršulis, Vladislovas; Vėjelis, Sigitas (Journal of Civil Engineering and Management, 2001)
The climatic parameters influence the equilibrium moisture of building enclosures and their thermal insulating layers. This investigation seeks to find a quantitative correlation between these influence values. The enclosure equilibrium moisture content W0 was expressed as the sum of two components: sorption moisture Ws and thermal condensation moisture Wt (formula 1). The coefficient η was introduced as the maintenance moist state criterion (formula 3), which depends on climatic conditions. It has been used for in-situ investigations of different enclosures (Fig 1) of dwelling houses as well as for damp and wet premises data [4–15]. The results (Fig 2, 3) show the dependence of equilibrium moisture on η. This dependence has been expressed by (4), where Wt0 is Wt component due to thermal condensation when η = 0. Wt0 is equal to 12,3% (vol) for ceramic and sand-lime, brick masonry as well as for porous concrete, expanded clay aggregate, slag fillings and is equal to 0,028% (vol) for rock wool products in traditional enclosures (Fig 1). The parameter α (7) was introduced for estimating cold season climate influence after mathematical statistical treatment of long-term climatic data [19]. It has been found (Table 1) that a may be adopted to be equal to 0,2 when the equilibrium moisture component due to thermal condensation has been calculated for Lithuanian climatic conditions. The possible equilibrium moisture of various building materials for enclosures has been evaluated by the proposed method and is given in Table 2. The data do not apply to expanded polystyrene, polyurethane foam and cellulose fibre because in-situ investigation data are absent for enclosures with these insulating materials. Table 2 shows that there are several distinctions in given values and corresponding values introduced in abrogated normative documents [25, 26] as well as corresponding corrections Δλw in valid documents [27] stipulated by additional moisture content of materials in enclosures. The correction value Δλw must be defined more precisely when thermal conductivity design values are calculated for enclosures with porous concrete or expanded clay aggregates.Santrauka. Išnagrinėtas atitvarinių konstrukcijų nuostoviojo drėgnio ryšys su skaičiuojamaisiais klimatiniais parameirais. Atitvarų nuosiovusis drėgnis W0 yra išreikštas sorbcinio Ws ir termokondensacinio Wt įdrėkio suma ir parodyta, kad koeficientas η (3) yra eksploaiacinio drėgminio būvio kriterijus. Atitvarų nuostoviojo drėgnio priklausomybė nuo kriterijaus η veriės pateikta (4). Čia Wt0 – termokondensacinis dėmuo Wt, kai η = 0. Bandymų duomenimis, jis lygus 12,3% (tūrio) pilnavidurių keraminių ir silikatinių plytų mūrui, taip pat akytajam betonui, keramzitbetoniui, šlakbetoniui, šlako užpildams ir – 0,028% (tūrio) akmens vatos gaminiams tradicinėse atitvarinėse konstrukcijose (1 pav.). Šaltojo periodo klimatui įvertinti taikytas parametras α ir nustatyta, kad skaičiuojant atitvarų nuostoviojo drėgnio termokondensacinį dėmenį Lietuvos klimato sąlygomis α = 0,2. Bandymų duomenimis ir atsižvelgiant į galimą klimato parametrų įtaką atitvarų drėgminiam būviui, atliktas galimų atitvarų statybinių medžiagų nuostoviojo drėgnio verčių, į kurias turėtų būti atsižvelgiama nustatant šių medžiagų šilumos laidumo projektines vertes, įvertinimas (2 lentelė).Article in Russian.First Published Online: 30 Jul 2012